Influence of sex and body composition on the plantar arch and postural control of children and adolescents from public school (Research, Society and Development, 2020)
To verify the influence of sex and body composition on the classification of the plantar arch and postural control of children and adolescents from public school. Cross-sectional observational study with a sample of 84 healthy children and adolescents, of both sexes, aged 11 to 14 years, from a public school in the city of Goiânia (GO), Brazil. The parents answered a questionnaire about the children's health history and the families' socioeconomic conditions. Participants were assessed through physical examination, foot evaluation and postural control using computerized baropodometry. The data of the evaluation of the plantar arches were analyzed statistically regarding the influence of sex and the classification of the body mass index (p ≤ 0.05%). The sample was mostly composed of neutral feet bilaterally, but girls had a higher frequency of hollow feet (29.09%) and boys with flat feet (3.45%). As for body composition, eutrophic girls showed greater pressure when compared to eutrophic boys, and overweight boys had greater pressure on their feet compared to the eutrophic group. As for postural control, eutrophic patients showed better performance in relation to the overweight group. The study revealed that the plantar arch and postural control of children and adolescents are influenced by sex and body composition.